2015
DOI: 10.1177/1533317515598859
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Medication Regimens is an Effective Indicator of Cognitive Dysfunction in Elderly Individuals

Abstract: Declining IADL scores in the shopping and responsibility for own medications categories may be effective indices for predicting early-stage cognitive dysfunction in elderly individuals. Cognitive dysfunction screening at pharmacy counters may be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Most studies that have examined the factors associated with sedentariness or inactivity have focused on psychosocial predictors. However, cognitive functions have recently been considered in adherence to treatment medication [ 12 , 13 ], but to our knowledge, no study has examined the predictive value of cognitive strategies in adherence to PA in healthy older adults. The aim of the present study was to identify cognitive and psychosocial determinants of the level of PA in independently living healthy older adults in France.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies that have examined the factors associated with sedentariness or inactivity have focused on psychosocial predictors. However, cognitive functions have recently been considered in adherence to treatment medication [ 12 , 13 ], but to our knowledge, no study has examined the predictive value of cognitive strategies in adherence to PA in healthy older adults. The aim of the present study was to identify cognitive and psychosocial determinants of the level of PA in independently living healthy older adults in France.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between cognitive functioning and adherence has been studied either by examining populations with cognitive impairments [ 12 , 13 ] or by training populations in cognitive processes [ 14 18 ]. These studies have been principally carried out in the context of medication adherence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…with late-life depression and AD, or both, are known to have significantly lower treatment adherence rates possibly linked to reduced cognitive functioning and a greater number of comorbidities [92,93]. Although adherence to SSRI's in people with AD is greater than adherence to Tricyclic antidepressants, over 50% of people with AD discontinue all antidepressant medication within 6 months [94].…”
Section: The Efficacy Of Ssri's In the Treatment Of Depression In Admentioning
confidence: 99%
“…[2] Changes in medication adherence may be an additional early indicator of cognitive impairment. [3] Studies have shown that cognitive abilities are important for optimal medication adherence in older adults. [49]…”
Section: Introductionmentioning
confidence: 99%